1997
DOI: 10.3168/jds.s0022-0302(97)76285-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Protein Standardization by Ultrafiltration on the Viscosity, Color, and Sensory Properties of Skim and 1% Milk

Abstract: Permeate and retentate (concentration factor ca. 2x) from UF of skim milk were combined, and cream was added to produce skim milk (0.1% fat) and 1% milk with a range of true protein contents (1.0 to 4.8%) within each fat level. A panel that had been trained for descriptive sensory analysis evaluated the appearance, aroma, flavor, and textural attributes of milks. Relative viscosity and Hunter color values for whiteness (L value), greenness to redness (a value), and blueness to yellowness (b value) increased wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 6 publications
2
37
0
Order By: Relevance
“…The measurement of the colour was used by others for establishing a relationship between a chemical characteristic and the physical properties of milk (Philippe et al, 2003;Quinones et al, 1997).…”
Section: Control Samplesmentioning
confidence: 99%
“…The measurement of the colour was used by others for establishing a relationship between a chemical characteristic and the physical properties of milk (Philippe et al, 2003;Quinones et al, 1997).…”
Section: Control Samplesmentioning
confidence: 99%
“…Altering the fat content (Frost et al, 2001;Phillips et al, 1995), protein content (Quinones et al, 1997, Quinones, Barbano, & Phillips, 1998, levels of defects such as oxidation (Lawless & Claassen, 1993), and other components of milk Phillips et al, 1995) have been shown to change the sensory properties of the milk, but no researchers have concentrated strictly on how the aftertaste of milk is altered when making such changes. Therefore, a fourth objective of this research was to examine several changes in milk for their ability to lessen the intensity and/or persistence of any of the aftertaste attributes.…”
Section: Introductionmentioning
confidence: 98%
“…Claassen and Lawless (1992) defined mouthcoating as Ôthe amount of residue remaining in the mouth, especially on the cheeks and tongue, after swallowing or expectorating.Õ They defined mouthdrying as Ôthe dryness, tightness, or roughness felt in the mouth after swallowing or expectoratingÕ, and irritation was defined as Ôthe sensation in the back of the throat associated with residue remaining after swallowing or expectoratingÕ. A number of researchers Phillips, McGiff, Barbano, & Lawless, 1995;Quinones, Barbano, & Phillips, 1997, 1998 have included the aftertaste terms ÔastringentÕ, Ôoverall residual flavorÕ, and Ôresidual mouthcoatingÕ in their descriptive analysis vocabularies for milk. Frost, Dijksterhuis, and Martens (2001) used the term Ôresidual mouth fillÕ, defined as the Ôdegree of residual mouthcoating after expectoration of the sampleÕ.…”
Section: Introductionmentioning
confidence: 99%
“…how milk sensory properties are affected by CLA (conjugated linoleic acid) fortification (Campbell, Drake, & Larick, 2003), lipolysis and proteolysis caused by storage (Wiking, Frøst, Larsen, & Nielsen, 2002), different levels of fat in milk (Frøst, Dijksterhuis, & Martens, 2001), and different levels of protein and fat (Quinones, Barbano, & Phillips, 1997 …”
Section: Introductionmentioning
confidence: 99%